Where is the Science? A Critical Interrogation of How Sex and Gender are Used to Inform Low-Risk Alcohol Use Guidelines. Issue 5 (September 2020) - Lowik, A.J.; Hoong, Peter; Knight, Rod
Abstract : N/A: Across the globe, many countries publish low-risk alcohol guidelines which outline the recommended best practices for drinking limits to reduce the health risks and harms associated with excessive alcohol use. Frequently, low-risk drinking guidelines include different recommendations for cisgender men and women. As researchers working in the area of trans-inclusive substance use treatment and care, we are interested in the rationale for how gender-based low-risk drinking guidelines are determined, including the role of evidence and science. We argue that low-risk drinking guidelines based on sex and/or gender are highly insufficient and not engaging with a robust evidence base, and we further argue that it is important that we attend to these concepts correctly as we develop clinical and public health guidelines, which will undeniably have an impact on the individuals and societies who rely on them. Abstract : Supplemental Digital Content is available in the text